2021
DOI: 10.12688/amrcopenres.13007.1
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility pilot study of the effects of neurostimulation on dysphagia recovery in Parkinson’s Disease

Abstract: Introduction: Dysphagia often occurs during Parkinson’s disease (PD) and can have severe consequences. Recently, neuromodulatory techniques have been used to treat neurogenic dysphagia. Here we aimed to compare the neurophysiological and swallowing effects of three different types of neurostimulation, 5 Hertz (Hz) repetitive transcranial magnetic stimulation (rTMS), 1 Hz rTMS and pharyngeal electrical stimulation (PES).   Method: 12 PD patients with dysphagia were randomised to receive either 5 Hz rTMS, 1 Hz r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Six included studies evaluated various forms of stimulation 34–39 . In general, these treatments can be classified into central and peripheral stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Six included studies evaluated various forms of stimulation 34–39 . In general, these treatments can be classified into central and peripheral stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a pilot study was published by Sasegbon et al, in 2021 in which PES was used to treat patients with Parkinson's associated dysphagia [121]. Although the technique was well tolerated in this patient group, low recruitment numbers resulted in a limited interpretation of the effects of PES in this population [121].…”
Section: Other Disease Processesmentioning
confidence: 97%
“…In this shamcontrolled study, PES resulted in significant improvements in electromyographic (EMG) recordings from external pharyngeal musculature and PAS scores at 2 weeks and 4 weeks post administration compared to sham [120]. More recently, a pilot study was published by Sasegbon et al, in 2021 in which PES was used to treat patients with Parkinson's associated dysphagia [121]. Although the technique was well tolerated in this patient group, low recruitment numbers resulted in a limited interpretation of the effects of PES in this population [121].…”
Section: Other Disease Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from stroke patients, some studies have also suggested that NIBS may also be beneficial to patients with multiple sclerosis (MS) 95 and PD. 96 Moreover, application of NIBS in the cerebellum has received increasing attention in recent years. Some studies suggested that cerebellar rTMS may be beneficial for patients with post-stroke dysphagia.…”
Section: Neuromodulation Treatmentsmentioning
confidence: 99%